Multidisciplinary approaches to language production - Pechmann, Thomas; Habel, Christopher (Trends in linguistics. Studies and monographs ;, 2004)
This volume comprises contributions from different disciplines (cognitive psychology, linguistics, computer science, neuroscience) concerned with the generation of natural speech. It summarizes the outcome of a six-year long priority program funded by the German Research Foundation (DFG) that aimed at bringing together colleagues with different viewpoints but sharing a principal interest in the cognitive processes underlying language production. The result is a state-of-the-art discussion of one of the most fascinating branches of human behavior taking into account a particularly rich multidis.